Characteristics of the Major Atmospheric Aromatic Hydrocarbons in the Yellow Sea - Park, Seung-Myung; Kim, Jeong-Soo; Lee, Gangwoong; Jang, Yuwoon; Lee, Meehye; Kang, Chang Hee; Sunwoo, Young (Asian journal of atmospheric environment (Online), 2015)
We measured the concentrations of five aromatic hydrocarbons (benzene, toluene, ethylbenzene, m,pxylene, and styrene) in the atmosphere during four seasonal campaigns at Deokjeok and Jeju Islands in the Yellow Sea from October 2005 to June 2006. Toluene was the most abundant aromatic hydrocarbon, with median of 0.24 ppb at Deokjeok and 0.20 ppb at Jeju, followed by benzene (0.21 ppb, 0.15 ppb) and m,p-xylene (0.06 ppb, 0.06 ppb). Aromatic hydrocarbon measurements exhibited the typical seasonality of the major emission sources, such as vehicle exhaust, solvent evaporation, and regional circulation patterns. The ratios of m,p-xylene/ethylbenzene of 1.57 at Deokjeok and 1.05 at Jeju reflected the degree of proximity to outflows of each source region, South Korea and China. The toluene/benzene ratios of 1.0 were consistently both on field observations and on the 3-D chemical model simulation, which is slightly higher than that in the Western Pacific area. It implied that the air over the Yellow Sea was influenced to a great extent by the surrounding areas. We confirmed that current emission inventories of aromatic hydrocarbons in Northeast Asia reasonably reproduced temporal and spatial variations of toluene and benzene over the Yellow Sea.